Predicting behavioral variant frontotemporal dementia with pattern classification in multi-center structural MRI data. - Meyer, S.; Mueller, K.; Stuke, K.; Bisenius, S.; Diehl-Schmid, J.; Jessen, F.; Kassubek, J.; Kornhuber, J.; Ludolph, A. C.; Prudlo, J.; Schneider, A.; Schuemberg, K.; et al. (Neuroimage Clin, 2017)
PURPOSE: Frontotemporal lobar degeneration (FTLD) is a common cause of early onset dementia. Behavioral variant frontotemporal dementia (bvFTD), its most common subtype, is characterized by deep alterations in behavior and personality. In 2011, new diagnostic criteria were suggested that incorporate imaging criteria into diagnostic algorithms. The study aimed at validating the potential of imaging criteria to individually predict diagnosis with machine learning algorithms. MATERIALS & METHODS: Brain atrophy was measured with structural magnetic resonance imaging (MRI) at 3 Tesla in a multi-centric cohort of 52 bvFTD patients and 52 healthy control subjects from the German FTLD Consortium's Study. Beside group comparisons, diagnosis bvFTD vs. controls was individually predicted in each subject with support vector machine classification in MRI data across the whole brain or in frontotemporal, insular regions, and basal ganglia known to be mainly affected based on recent meta-analyses. Multi-center effects were controlled for with a new method, "leave one center out" conjunction analyses, i.e. repeatedly excluding subjects from each center from the analysis. RESULTS: Group comparisons revealed atrophy in, most consistently, the frontal lobe in bvFTD beside alterations in the insula, basal ganglia and temporal lobe. Most remarkably, support vector machine classification enabled predicting diagnosis in single patients with a high accuracy of up to 84.6%, where accuracy was highest in a region-of-interest approach focusing on frontotemporal, insular regions, and basal ganglia in comparison with the whole brain approach. CONCLUSION: Our study demonstrates that MRI, a widespread imaging technology, can individually identify bvFTD with high accuracy in multi-center imaging data, paving the road to personalized diagnostic approaches in the future.
Keywords: Aged; Atrophy/diagnostic imaging; Brain/*diagnostic imaging/pathology; Brain Mapping; Cohort Studies; Female; Frontotemporal Dementia/*diagnostic imaging/*physiopathology; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging/*methods; Male; Middle Aged; Predictive Value of Tests; Support Vector Machine